Comprehensive periodic evaluation of Oryza sativa germplasms for resistance against rice root-knot nematode, Meloidogyne graminicola - Berliner, J; Pokhare, SS; Mishra, CD; Sahoo, SC; Munda, S; Adak, T; Bose, LK; Marandi, BC; Subudhi, HN; Patra, BC; Manimaran, B (ORYZA-An International Journal of Rice, 2022)
Rice root knot nematode, Meloidogyne graminicola is an important nematode pest with a devastating potential that causes serious damage to rice crop. There is an intensive search for eco-friendly, sustainable alternative to the existing nematode management practices. Host plant resistance offers propitious results in managing this minuscule crop enemy. Preliminary screening of 1731 Oryza sativa germplasms followed by periodic evaluation of nine resistant / tolerant germplasms shed new insights on nematode resistance. We observed seasonal inconsistency in the resistance in previously reported germplasms ’Ramakrishna’, ’TKM6’, ’Abhisek’, ’Laxman sal’, ’Ratna’, and ’TKM1’. Hence, we strongly recommend repeated screening of identified resistant/tolerant rice germplasm lines against M. graminicola in both winter and summer season to confirm the consistency in resistance scale. Further investigation is needed to nullify other chance factors like nematode pathotypes.